Effectiveness and safety of an atropine/midazolam and target controlled infusion propofol-based moderate sedation protocol during percutaneous endoscopic transgastric jejunostomy procedures in Parkinson’s disease: a real-life retrospective observational study - Gravina, Antonietta Gerarda; Pellegrino, Raffaele; De Micco, Rosa; Dellavalle, Mirco; Grasso, Anna; Palladino, Giovanna; Satolli, Sara; Ciaravola, Massimo; Federico, Alessandro; Tessitore, Alessandro; Romano, Marco; Ferraro, Fausto (Frontiers in Medicine, 2023)
Patients with Parkinson's disease (PD), often elderly with various comorbidities, may require a continuous intestinal infusion of carbidopa/levodopa gel by the placement of a percutaneous endoscopic gastrostomy (PEG) with a jejunal tube (PEG-J) to improve their motor outcome and quality of life. However, it is unclear what is the best procedural sedation protocol for PEG-J procedures. Fifty patients with PD and indication for PEG-J procedure (implantation, replacement, removal) underwent, from 2017 to 2022, a sedation protocol characterized by premedication with atropine (0.01 mg/Kg i.v.), midazolam (0.015 – 0.03 mg/Kg i.v.) and induction with bolus propofol (0.5 – 1 mg/Kg i.v.) as well as, finally, sedation with continuous infusion propofol (2-5 mg/Kg/h i.v.) by Target Controlled Infusion (TCI) technique. Ninety-eight per cent of patients experienced no intraprocedural or peri-procedural adverse events. All the procedures were technically successful. A good discharge time was recorded. The vital parameters recorded during the procedure did not vary significantly. A PEG-J procedure conducted within 30 minutes showed a significant advantage over end-tidal carbon dioxide (EtCO2). The latter was, in turn, found to be a predictor to follow for conducting the procedure within 30 minutes (OR: 1.318, 95% CI 1.075 - 1.615, p=0.008). In the real world, this sedation protocol showed a good safety and effectiveness profile, even with reduced doses of midazolam and a TCI propofol technique in moderate sedation.